Simultaneous quantification of dasatinib, nilotinib, bosutinib, and ponatinib using high‐performance liquid chromatography–Photodiode array detection. Issue 8 (12th July 2022) - Yokoyama, Yuta; Nozawa, Eiji; Morita, Miho; Ishikawa, Emi; Mori, Takehiko; Sakurai, Masatoshi; Kikuchi, Taku; Matsuki, Eri; Yamazaki, Rie; Kataoka, Keisuke; Jibiki, Aya; Kawazoe, Hitoshi; et al.
Abstract: Background: Dasatinib, nilotinib, and bosutinib, second‐generation tyrosine kinase inhibitors (TKIs), and ponatinib, a third‐generation TKI, are approved pharmaceuticals used in the treatment of chronic myeloid leukemia (CML). Although liquid chromatography‐tandem mass spectrometry assays for simultaneous quantification of the four TKIs in human serum have been reported in the literature, a high‐performance liquid chromatography (HPLC) assay that simultaneously quantifies these compounds has not yet been developed. This study aims to establish and validate an efficient HPLC analytical method using a photodiode array (PDA) detector for the simultaneous quantification of the four TKIs. Methods: Calibration standards were prepared by serial dilution of serum samples containing the four TKIs, followed by solid‐phase extraction. The four TKIs were eluted in order within 10 min using a binary HPLC gradient system. Results: The calibration ranges were 2–500 ng/ml for dasatinib, 100–5000 ng/ml for nilotinib, and 10–500 ng/ml for bosutinib and ponatinib. Intra‐day and inter‐day precision and accuracy values were found to be in accordance with the U.S. Food and Drug Administration guidelines. The recovery rates were 92.9%–96.0%, 80.7%–86.1%, 91.6%–99.0%, and 86.4%–92.6% for dasatinib, nilotinib, bosutinib, and ponatinib, respectively. Conclusion: To the best of our knowledge, this is the first report of an HPLC‐PDA analytical method that allows efficient simultaneous quantification of the four TKIs in the serum of patients with CML. We believe that the method developed herein can improve the efficiency of therapeutic drug monitoring in patients with CML in clinical practice. Abstract : We established the first HPLC‐PDA analytical method for simple and rapid simultaneous quantification in serum concentration of dasatinib, nilotinib, bosutinib, and ponatinib. This HPLC‐PDA method can be applied to the TDM of the four TKIs for CML patients, enabling the construction of an optimal dosing regimen.